1-36b2

Rewrite 1 as 12.

12-36b2

Rewrite 36b2 as (6b)2.

12-(6b)2

Since both terms are perfect squares, factor using the difference of squares formula, a2-b2=(a+b)(a-b) where a=1 and b=6b.

(1+6b)(1-(6b))

Multiply 6 by -1.

(1+6b)(1-6b)

Factor 1-36b^2

Skip to content
# Factor 1-36b^2

1-36b2

Rewrite 1 as 12.

12-36b2

Rewrite 36b2 as (6b)2.

12-(6b)2

Since both terms are perfect squares, factor using the difference of squares formula, a2-b2=(a+b)(a-b) where a=1 and b=6b.

(1+6b)(1-(6b))

Multiply 6 by -1.

(1+6b)(1-6b)

Factor 1-36b^2